Effect of pressure on density, porosity and flexural strength during cold isostatic press of alumina-ysz chromia cutting too - Norfauzi, T.; Hadzley, A. B.; Azlan, U. A. A.; Azhar, A. A.; Noorazizi, S. (2021)
This study presented the effect of pressure on the density, porosity and flexural strength when cold isostatic press (CIP) was applied to compact the ceramic powders in the form of insert cutting tools. Specific composition of alumina (Al2O3) wt.90%,yittria stabilized zirconia (YSZ) wt.10%, chromium oxide(Cr2O3) wt.0.6% and polyethylene glycol (PEG) wt.0.6% were ball milled and hand pressed to form green body of ceramic inserts. These green body were undergone further compaction inside CIP with pressures variation of 200 MPa, 300 MPa, 400 MPa with 30 seconds and 60 seconds pressuring time. The ceramic composts were then sintered at 1440°C for 9 hours before being assessed with density, porosity, Rockwell hardness (HRC) and bending test. The results show that CIP use with 300 MPa parameters with 60 seconds shows the best mechanical properties with relative density 95.5%, porosity 4.5% and HRC 65.5 hardness. Further assessment of microstructure revealed that the particles size distributed evenly along fracture surface with coarse grain and porosity dominant in the certain area.